2022
DOI: 10.1007/s10067-022-06106-1
|View full text |Cite
|
Sign up to set email alerts
|

Flare of adult-onset Still’s disease following mRNA COVID-19 vaccination: a case report and review of literature

Abstract: The upheaval caused by the coronavirus disease 2019 (COVID-19) pandemic has allowed to large population to use new vaccines urgently. Although vaccine development programs and available epidemiological data reassure us, there are concerns about specific risks associated with vaccinations in patients with autoimmune-autoinflammatory diseases. These patients have the potential to decrease humoral and cellular immune responses caused by biologic agents and develop an acute flare of underlying disease following va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In certain cases, genetic studies may be useful to exclude hereditary autoinflammatory diseases, but do not show sufficient diagnostic precision to be routinely recommended in AOSD work-up [12,31,42,97,189,211]. From a diagnostic perspective, it is noteworthy that flares or primary manifestations of AOSD have been noted in temporal relation to COVID vaccinations during the course of the current pandemic [99,123,145,159,172,212]. Concerning therapeutic options, the board decided against phrasing a recommendation for or against tumor necrosis factor (TNF)-blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, genetic studies may be useful to exclude hereditary autoinflammatory diseases, but do not show sufficient diagnostic precision to be routinely recommended in AOSD work-up [12,31,42,97,189,211]. From a diagnostic perspective, it is noteworthy that flares or primary manifestations of AOSD have been noted in temporal relation to COVID vaccinations during the course of the current pandemic [99,123,145,159,172,212]. Concerning therapeutic options, the board decided against phrasing a recommendation for or against tumor necrosis factor (TNF)-blocking agents.…”
Section: Discussionmentioning
confidence: 99%
“…We herein report three cases of AOSD that developed following vaccination with mRNA COVID-19 vaccines (two with BNT162b2 and one with mRNA-1273). To our knowledge, 10 other cases of new-onset (cases 1-10 in the Table ) and relapse of AOSD (cases 14-17 in Table ) have been reported following COVID-19 vaccination ( 13 - 23 ). Seven of those 10 patients developed symptoms 5-21 days after the first or second dose of the COVID-19 vaccine ( Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported AOSD that developed after influenza vaccination; since 2021, cases of new-onset AOSD and relapsed immune-mediated disease have also occurred after COVID-19 vaccination (7,8,10,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). There are two main types of COVID-19 vaccine formulations: mRNA encoding the SARS-CoV-2 spike protein (S) encapsulated in lipid nanoparticles or adenovirus (AdV) vectors encoding the S protein (35).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection could also induce cytokine storms driven by IL-6, IL-1α, IL-1β, and TNF-α [ 42 ], and the pathogenesis of both is similar. Multiple case reports have shown that vaccination against COVID-19 can induce a strong immune response [ 43 , 44 ]. However, it is not possible to distinguish whether an adverse effect of vaccination is the induction of new-onset AOSD or whether it is actually a relapse of existing AOSD that plays a major part in this mechanism.…”
Section: Discussionmentioning
confidence: 99%